Overview of how HCMV manipulation of host cell intracellular trafficking networks can promote productive infection - Mosher, Bailey S.; Kowalik, Timothy F.; Yurochko, Andrew D. (Frontiers in Virology, 2022)
Human cytomegalovirus (HCMV) is a significant cause of morbidity and mortality in the immunocompromised and developing fetuses. Infection has also been linked to chronic inflammatory diseases, cardiovascular disease, and the development of certain cancers. The wide range of pathologies associated with HCMV infection is attributable to the broad cellular tropism of the virus where infection affects every organ system. Like other viruses, HCMV must tailor host cells to support productive infection. In particular, HCMV dedicates many resources and various strategies to manipulate host intracellular trafficking networks to facilitate various aspects of infection across all infected cell types. The dysregulation of host intracellular trafficking networks allows the virus to translocate to the host cell nucleus for genome replication, facilitate nuclear import/export of viral proteins and immature virions, subvert the host immune response, form new organelles for progeny virion assembly, maturation and egress, and promote cellular migration and viral spread. However, due to their complex nature, many aspects of these processes are not well-studied. New research and omics-based technologies have recently begun to elucidate the extent to which HCMV dysregulates host cell trafficking machinery. Here we review the variety of strategies HCMV utilizes to dysregulate intracellular trafficking networks to promote productive infection.